Pesticides: A Perspective of Scientific Production in West of Bahia - José Domingos Santos da Silva; Michely Oliveira Madureira; Gabriel Macêdo dos Anjos; Caroline Oliveira Pinto; Oldair Donizeti Leite; João Victor da Silva Santos (Orbital: The Electronic Journal of Chemistry, 2017)
The use of pesticides has intensified with agricultural modernization process, triggered by the Green Revolution, which brought about changes in the production system, resulting in high social costs, environmental and public health. Brazil is the world's largest consumer of pesticides and assesses that this market will grow even more in the near future. Given the risk that pesticides pose, it was found that there is an urgent need to intensify the studies, as are scarce research in the Northeast and especially in western Bahia. This research aimed to evaluate the scientific literature on pesticides in West of Bahia. Therefore, publications consultation was made in the database Portal.periodicos.Capes with the keywords "West of Bahia" and "Pesticides". The results show that the number of worldwide publications has been growing over the years, representing 98% of the total, while Brazil has only 2% in West of Bahia was not found publication. There are many challenges in front of the dimension that the theme "pesticide" offers. Thus, priorities and strategies for research should be defined, seeking to boost scientific productivity in an attempt to make changes to help chart a way to sustainable development.DOI: http://dx.doi.org/10.17807/orbital.v9i2.909